Pusat Service Tayar Bahagia Sdn. Bhd. / Fairuq Asraf Sulaiman ... [et al.] - Sulaiman, Fairuq Asraf; Rudin, Mohd Kamarul Nizam; Ismail, Redzwan Khaled; Mustafa Kamal, Mohd Khairul; Kamarudin, Muhammad Ikram (Faculty of Civil Engineering, 2005)
The administration board of the company has agreed upon the official name of the company. Thereof the official name of the company is Pusat Servis Tayar Bahagia Sdn. Bhd